Femoral Condyle Measurements in Anterior Cruciate Ligament Injury: 1 Tesla Magnetic Resonance Imaging Analysis: Femoral Condyle Measurements in Ligament Injury - Khan, Mohib Ullah; Ullah, Hidayat; Ahmad, Saeed; Khan, Jawad; Askar, Zahid; Iqbal, Malik Javed (Pakistan Journal of Health Sciences, 2025)
Orthopedic injury of Anterior Cruciate Ligament (ACL) remains an increasingly frequent issue that primarily affects athletes with permanent complications as a result. The modern Magnetic Resonance Imaging (MRI) technology enables better accuracy when measuring femoral condyles. Objective: To investigate the dimension analysis of the femoral condyles regarding ACL injuries alongside their implications for both surgical procedures and preventive management. Methods: Descriptive cross-sectional study from September 2023 to August 2024 in the Orthopedic department. The study enrolled 385 participants between 18 to 60 years old. All subjects completed scanning with a 1 Tesla MRI and the researchers recorded femoral condyle dimensions. Data analysis occurred with SPSS version 26.0. while linear regression and ANOVA. Results: The research analysis involved 385 participants whose mean age equaled 34.7 ± 6.95 years. The majority were male (70.6%). Mean measurement of Lateral Condyle AP was 6.28 ± 0.43 cm while Medial Condyle AP recorded 6.11 ± 0.46 cm, and Trans-epicondylar Axis reached 7.96 ± 0.53 cm. ANOVA analysis found significant measurement distinctions in knee joints that occurred between different age groups (p<0.001). The results from independent t-tests showed knee measurement discrepancies between men and women signify statistical significance at p<0.001. Conclusions: This research demonstrated that the dimensions of femoral condyles act as major factors that determine risk for ACL injuries. Preventive strategies alongside treatment plans for ACL injuries need to adopt age- and sex-specific considerations according to the research results.